Endogenous technology, scarring and fiscal policy - Michaela Elfsbacka Schmöller (Bank of Finland, 2022)
This paper studies fiscal policy in a New Keynesian DSGE model with endogenous technology growth in which scarring can occur endogenously through hysteresis effects in TFP. Both demand- and supply-driven recessions can weaken investment in R&D and technology adoption, thus depressing the long-run trend. Fiscal policy has long-term effects under endogenous growth and the type of fiscal stimulus is decisive for the sign and magnitude of fiscal multipliers. Expansionary government spending boosts output transitorily but over time crowding out in technology-enhancing investment weakens the long-run trend. I introduce fiscal growth policies in this environment which in the short run raise aggregate demand and simultaneously support growth-enhancing investment and thus the long-run trend, generating a positive trend multiplier. Multipliers of fiscal growth policies can be sizeable, above all when targeted to R&D, which is characterized by fiscal multipliers greater than unity. The importance of monetary-fiscal interaction is amplified due to long-run non-neutrality of monetary policy.
Keywords: E24; E31; E32; E52; E62; O42; 330; Fiscal Multiplier; Hysteresis; Endogenous Growth; Inflation; Monetary-Fiscal Interaction